2011
DOI: 10.1128/aem.02201-10
|View full text |Cite
|
Sign up to set email alerts
|

Induction of a State of Iron Limitation in Uropathogenic Escherichia coli CFT073 by Cranberry-Derived Proanthocyanidins as Revealed by Microarray Analysis

Abstract: Transcriptional profiles of uropathogenic Escherichia coli CFT073 exposed to cranberry-derived proanthocyanidins (PACs) were determined. Our results indicate that bacteria grown on media supplemented with PACs were iron deprived. To our knowledge, this is the first time that PACs have been shown to induce a state of iron limitation in this bacterium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 32 publications
2
29
0
2
Order By: Relevance
“…A whole-transcriptome analysis of UPEC CFT073 grown in LB in the presence or absence of 0.1 mg/ml cPACs was conducted previously by our lab (15). The study revealed that in the culture grown with cPACs, the flagellin gene (fliC) was downregulated 2.4-fold (15).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A whole-transcriptome analysis of UPEC CFT073 grown in LB in the presence or absence of 0.1 mg/ml cPACs was conducted previously by our lab (15). The study revealed that in the culture grown with cPACs, the flagellin gene (fliC) was downregulated 2.4-fold (15).…”
Section: Resultsmentioning
confidence: 99%
“…Among the genes that were found to be downregulated in the presence of cPACs was the flagellin gene (fliC) (15). Additional research has shown that in Pseudomonas aeruginosa, swarming motility is blocked by cPACs and other tannins (36).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Cranberry proanthocyanidins have also been shown to bind iron strongly through the orthodihydroxy group of the B-ring [9]. The effect of iron sequestration by these compounds can be seen by differential gene expressions in E. coli in particular genes involved in up-regulation of the iron acquisition systems [20,21]. Tannic acid, a water-soluble phenolic compound found in many fruits and vegetables (including cranberries) was postulated to inhibit the growth of E. coli, Salmonella enteric serotype Typhimurium and various Clostridia pathogens through iron sequestration [22].…”
Section: Introductionmentioning
confidence: 99%